1997
DOI: 10.1159/000185369
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Robinow Syndrome Accompanied by Partial Growth Hormone Insufficiency Treated with Growth Hormone

Abstract: We report on a 10-year-old Japanese girl with Robinow syndrome accompanied by partial growth hormone (GH) insufficiency. We started GH replacement therapy at the chronological age of 6.5 years. In this case, improvement in the growth velocity was remarkable, but bone maturation accelerated even more. In order to avoid further acceleration of bone maturation, we started to treat our patient at the chronological age of 9.8 years with GH combined with gonadal suppression therapy using a luteinizing hormone releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…His bone age at diagnosis was not significantly retarded in comparison to his chronological age, similar to other genetic syndromes accompanied by GH deficiency, such as Robinow syndrome 6 . He is the first patient with cerebrofaciothoracic dysplasia presenting GH deficiency, as already reported 5 .…”
Section: Discussionsupporting
confidence: 57%
“…His bone age at diagnosis was not significantly retarded in comparison to his chronological age, similar to other genetic syndromes accompanied by GH deficiency, such as Robinow syndrome 6 . He is the first patient with cerebrofaciothoracic dysplasia presenting GH deficiency, as already reported 5 .…”
Section: Discussionsupporting
confidence: 57%
“…Eventually, at an optimal age after growth has been achieved, he will need surgical intervention in the form of anterior bone graft and posterior hook and rod system to achieve an anterior and posterior arthrodesis. Kawai et al 2 reported on a 10 year-old girl with Robinow syndrome with GH deficiency who also had a remarkable improvement in her growth velocity during replacement therapy with GH. Therapy had to be discontinued for some time in VOLUME 12, NO.…”
Section: Journal Of Pediatric Endocrinology and Metabolismmentioning
confidence: 99%
“…He started growth hormone replacement at 4 years and consistently improved, reaching the 44 th percentile in height (Figure 4). To date, his height is 155.6 cm (-0.14 SDS) 2,6,9,12,17 . The patient's last bone age reported was 13.16 (Greulich & Pyle), with a chronological age of 12.6 years.…”
Section: Treatmentmentioning
confidence: 99%